Strength and Microstructural Changes in Cementitious Composites Containing Waste Oyster Shell Powder - Min Ook Kim; Myung Kue Lee (Buildings, 2023)
In this study, the effect of adding waste oyster shell powder (WOSP) on the strength and microstructure of cementitious composites was experimentally investigated. The test variables included the WOSP replacement ratios (0, 25, 50, and 75%) by weight of cement, the type of curing water (tap water and seawater), and the curing period (7, 28, 90, 180, and 365 d). The compressive strength, flexural strength, and initial and secondary sorptivity were measured at specific ages. Moreover, scanning electron microscopy (SEM) and X-ray diffraction (XRD) measurements were conducted, and their results were analyzed. Samples with WOSP replacement ratios greater than 25% exhibited a rapid reduction in measured strength values. The correlation between compressive strength and initial sorptivity tends to be slightly higher than that between flexural strength and initial sorptivity. The one-year investigation revealed that there was no significant effect of using different curing waters on strength development. The effect of the curing period was evident in enhancing the strength only in the early stages, with no significant increase in strength observed after 28 d. The XRD analysis revealed that most samples prepared with WOSP contained CaCO3, and the peak of CaCO3 tended to increase with an increasing WOSP replacement ratio. The SEM results revealed that a high replacement ratio of WOSP can have a negative influence on cement hydration and the pozzolanic effect. The limitations of this study and future work were also discussed.